Combining CBT and medication : an evidence-based approach - Sudak, Donna M. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Combining medication and cognitive behavioral therapy (CBT) can be challenging but can also enhance patient care. This book reviews the existing literature about the neurobiological and clinical basis in combining CBT and medication for non-psychiatrist mental health clinicians. Filled with case studies drawn from the author's extensive clinical and teaching experience, this book breaks new ground in bringing together the most current, proven protocols for using drugs and CBT to improve client care. Practitioners will find in this volume the tools to make informed recommendations to patients'--Provided by publisher.
Includes bibliographical references (p. 209-234) and index.
Keywords: Cognitive therapy; Mental illness -- Chemotherapy